Digital Comic Strips as Multi-Modal Text for Learning Interpersonal and Transactional Text in Junior High School: A Content Analysis - Pratiwi, Anisa; Palupi, Tara Mustikaning (STAIRS: English Language Education Journal, 2022)
This research aimed to analyze the content of the digital comic strips for learning interpersonal and transactional text at Junior High School levels. The research was conducted based on the research questions: (1) How is the suitability of the digital comic strips used for grade 8 Junior High School in terms of the content of the interpersonal and transactional text? (2) How do the digital comic strips meet the criteria of digital learning material? The research used qualitative content analysis the instrument of which was adapted from the Indonesia Minister of Education and Culture Indonesia Syllabus and three Digital Learning Material Framework. The data was sourced from the digital comic strips uploaded on social media and comic strips web. It was revealed that 95% of all of the digital comic strips already have the language features that the Indonesia Education and Culture Minister stated on the syllabus, also accomplish the digital material learning criteria from accessibility and content by The National Center for Accessible Educational Resources (AEM), PRIMO (Peer-Reviewed Instructional Materials Online) Selection Criteria, and Petri Nokelainen. The findings revealed promising future to use digital comic strips as an instructional reading materials.